MORFOLOGI DAN ANATOMI TANAMAN KELOR (Moringa oleifera L.) PADA BERBAGAI KETINGGIAN TEMPAT TUMBUH - Sandi, Amir; Sangadji, Muh Nur; Samudin, Sakka (AGROTEKBIS, 2019)
The aim of this experiment is to study the morphology and anatomy of moringa plant at various height grow place in area of Palu, Sigi and Palolo. This research used the method survey and direct measurement. First activity was to determine the research location. Determination of research location was by purpose sampling, that is in height of ± 150; ± 300; ± 450; and > 451 masl, every altitude place was selected by random as much as 7 moringa crop, so that as a whole moringa crop in requiring as much 28 tree. Individual difference of observed tree of moringa based on the morphology and leaf anatomy, to conclude the difference of morphology and antomi, all the data gathered were analysed by calculating the distance of Euclid constructively program the SYSTAT 8.0. Research result indicated that there are difference of morphology and anatomy of leaf of moringa plant (Moringa oleifera L.) at different height place. Morphology character differentiating for example leaf length, wide of leaf, anatomy character that is closeness stomata, number of epidermis, and make an index to stomata.